Astylus variegatus (Coleoptera, Melyridae): cytogenetic study of a population exposed to agrochemical products - Schneider, Marielle Cristina; Carraro, Bianca Pierina; Cella, Doralice Maria; Matiello, Rodrigo Rodrigues; Artoni, Roberto Ferreira; Almeida, Mara Cristina de (My University, 2007)
In this work we describe the cytogenetic analyses performed in specimens of Astylus variegatus (Germar, 1824) collected in two localities: one area of natural vegetation and one of agricultural crops, where agrochemical products were used. Astylus variegatus had karyotypes with 2n(male) = 16+Xypand 2n (female) = 16+XXp, with exclusively metacentric chromosomes. Pachytene spermatocytes showed synapsed autosomal bivalents and non-associated sex chromosomes. In diplotene, the autosomal bivalents exhibited one or two terminal chiasmata and the Xyphad a typical parachute configuration. In meiotic cells of some specimens, an extra chromosome, interpreted as a B chromosome, was observed. C-banding showed constitutive heterochromatin in the pericentromeric region of all chromosomes, with the exception of the yp. Silver nitrate staining revealed one nucleolus organizer region (NOR) on the terminal region of the short arm of the second autosome pair. Silver staining of meiotic cells confirmed the NOR pattern detected in mitotic cells and revealed an argentophilous material on the Xyp. A cytogenetic comparison between the two populations of A. variegatus showed a statistically significant divergence (2= 117.10; df = 1) in the number of aneuploid cells and a higher frequency of B chromosome in the population exposed to agrochemicals.
Keywords: B chromosome; Constitutive heterochromatin; Karyotype; Meiosis; Ag-NORs